2008
DOI: 10.12968/bjom.2008.16.9.30888
|View full text |Cite
|
Sign up to set email alerts
|

Role modelling in the clinical workplace

Abstract: To ensure pre-registered midwifery students are fit for practice, it is recommended that when students attend their clinical placements they are allocated to work alongside mentors who have undertaken mentorship training and, more recently have fulfilled additional criteria, that ensures they are fully qualified (Nursing & Midwifery Council (NMC), 2006). This article aims to assist midwives who are considering enrolling on a mentorship programme. The paper illustrates how Bandura's (1977) model of behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
0
19
0
3
Order By: Relevance
“…Role modelling is an excellent way to transmit positive values and attitudes (Armstrong, ). The students in this study felt supported when they received compassion and respect from both clinical and academic staff as it was when these personal qualities were shown that the students felt able to ask for help and support with their work.…”
Section: Discussionmentioning
confidence: 99%
“…Role modelling is an excellent way to transmit positive values and attitudes (Armstrong, ). The students in this study felt supported when they received compassion and respect from both clinical and academic staff as it was when these personal qualities were shown that the students felt able to ask for help and support with their work.…”
Section: Discussionmentioning
confidence: 99%
“…Role modelling is also identified as a powerful agent or enabler of professional development (Illingworth 2009, Klunklin et al 2011, Timmins 2011, Pestka et al 2012. It reinforces approaches to leadership and delivery of care that other staff can aspire to (Armstrong 2008, Price & Price 2009, Kenward & Kenward 2011. Role models are mindful of the effects of role modelling in relation to interpersonal communication and will consciously choose to act in a particular way knowing that others are observing.…”
Section: Introductionmentioning
confidence: 91%
“…Professional development opportunities in the clinical setting range from the more formal such as clinical teaching, and the less formal but equally important behaviours such as role modelling. Clinical teaching that occurs during the normal course of duties can provide valuable opportunities for professional development and knowledge exchange (Allan et al 2008, Armstrong 2008, Price & Price 2009, Felstead 2013. These real-life scenarios allow undergraduate nursing students and less experienced nurses to develop skills and expertise in a supportive and safe learning environment (Armstrong 2008, Felstead 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive role models can have a constructive influence on students and colleagues by providing encouragement toward learning and professional development. Indeed, Armstrong (2008) argued that role models have an important responsibility to be "gatekeepers" to learning. However, it is not clear what frontline mental health nurses think about role models.…”
mentioning
confidence: 99%